A survey of the use of the vernacular as medium of instruction in twelve Philippine public schools with particular reference to Iloilo - Jardenil, Neva A. 1928-
This study provides supplementary information on the use of the vernacular as medium of instruction. First part of the paper is a survey of attitudes and problems on the use of vernacular, and the second part is a follow-up of the Iloilo experiment.